Quantization procedure for non-Abelian chiral bosons - Abdalla, E.; Abdalla, M. C.B. [UNESP] (My University, 1989)
Chiral bosonic fields are described by the Wess-Zumino-Witten action with second-class constraints. The system is quantized via the Dirac procedure, and a realization of the quantum field theory is defined by the conformal algebra. The relation to fermions is briefly discussed. © 1989 The American Physical Society.